2017
DOI: 10.5530/jyp.2017.9.18
|View full text |Cite
|
Sign up to set email alerts
|

Use of Okra Mucilage and Chitosan Acetate in Verapamil Hydrochloride buccal patches development; In vitro and Ex vivo Characterization

Abstract: Objective: Transmucosal buccal drug delivery could be an alternative for oral administration for systemic delivery of Verapamil Hydrochloride (VH), as it has low bioavailability 20 -35 % due to its extensive first pass metabolism and variable absorption at GIT. Method: Buccal patches of VH were prepared by solvent casting method using bioadhesive polymers HPMC K4M, Carbopol 934P, Chitosan acetate and Okra mucilage isolated from Hibiscus esculantus fruits, in various combinations as per 2 4 half factorial model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The drug content was determined as mean of three determinations using standard calibration curve. Percentage moisture content was determined in triplicate for each batch since moisture in the film could be crucial as it affects the mechanical strength, adhesive properties, and friability of film [10].…”
Section: Drug Content and % Moisture Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…The drug content was determined as mean of three determinations using standard calibration curve. Percentage moisture content was determined in triplicate for each batch since moisture in the film could be crucial as it affects the mechanical strength, adhesive properties, and friability of film [10].…”
Section: Drug Content and % Moisture Contentmentioning
confidence: 99%
“…The DT was noted for each film at which film started to break apart. All the studies were performed in triplicate for each batch [10].…”
Section: Disintegration Timementioning
confidence: 99%
“…Studies that characterized okra mucilage have reported its physicochemical and rheological properties for pharmaceutical applications and its use as a natural additive in food products and nutraceutical supplements ( Figure 2 ) [ 74 , 75 , 76 , 77 , 78 ]. The main potential applications of okra polysaccharides in different industries are described below.…”
Section: Applications Of Okra Mucilagementioning
confidence: 99%
“…The EC layer of the testing buccal tablet was glued at the bottom of a glass vial connected with the balance. The tablet (mucoadhesive core layer) was allowed to contact with porcine buccal membrane for 5 min with a load weight of 5 g. Next, the load weight was removed and the weight (g) required to detach the adhered tablet from the mucous membrane was measured as described by Navamanisubramanian et al 28…”
Section: Ex Vivo Mucoadhesion Strengthmentioning
confidence: 99%